Peran Komunikasi Dakwah di Era Digital Upaya Maksimal Pembelajaran Agama Islam - Hayat, Naila Mafayiziya; Riam, Zaenal Abidin (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2022)
Da'wah is a vital element in the Islamic world. The acceptance and implementation of Islamic teachings within society are influenced by the intensity of da'wah; the more intensive the da'wah, the more deeply rooted Islamic values become in people's daily lives. Da'wah is inseparable from communication, as the process of da'wah inherently involves communication. In essence, communication plays a key role in the success of da'wah activities, especially in the digital era. The success or failure of a da'i’s (Islamic preacher’s) mission is largely determined by their communication skills. Effective communication serves as a crucial asset for da'is to convey their messages in an efficient and impactful manner. In the digital era, communication plays three important roles in the realm of da'wah. First, it helps da'is understand the characteristics of society in the digital age. Second, it ensures that the message of da'wah is delivered effectively. Third, it facilitates the delivery of da'wah messages across all segments of society.